Participation of reactive oxygen species in the self-regulation of cardiac contractile function - V. I. Kapelko (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The article analyzes various mechanisms of ROS participation in the processes that determine the response of automatism and cardiac contractile function under natural short- or long-term physiological stress, and acute disturbance of energy production in cardiomyocytes. Superoxide and hydrogen peroxide are believed to have a similar effect, while the effect of nitroxide noticeably different. It was noted that increased CA++ in bioplasma not only enhances the contraction of myofibrils, but at the same time accelerates the rate of ATP synthesis. Regulation of volume load on the cellular level is realized by stretching of the sarcomeres, which increases the degree of actomyosin interaction. This corresponds to increase in the number of CA++ activators. Perhaps the formation of ROS in cardiomyocytes in response to stretching is a permanent and mandatory component of physiological responses that can synchronize the release of CA++ from SR and modulate its magnitude. However, in pathological conditions, overproduction of ROS can trigger arrhythmogenic CA++ waves. Some changes of DNA molecules under the influence of ROS may also be helpful to consolidate as a result of natural selection. Reactive oxygen species (ROS) are often considered as selected in the course of evolution as means of combating a variety of infections, but in the course of phylogeny they also were selected as a means of intracellular and extracellular exchange of information.